Evaluation of sunflower germplasms for salt tolerance based on morpho-physiological and yield attributes - Zulfiqar, Md.; Tajkia, Jannat E; Islam, Md. Tariqul; Mia, Md. Ashik; Hossain, A.K.M. Zakir (Archives of Agriculture and Environmental Science, 2025)
The effects of salinity on sunflower (Helianthus annuus L.) germplasms growth, morpho-physiological traits and yield attributes among six varieties was studied to identify potential salt-tolerant sunflower varieties for cultivation in saline-prone areas of Bangladesh. For this, an experiment was conducted at Bangladesh Agricultural University in a net house from January 2019 to May 2019. Results showed that all varieties of sunflower exhibited significant (p<0.05) alterations to morphological characteristics aside from stem diameter under salt stress conditions. The physiological changes were also induced, except for one measure of photochemical efficiency. Notably, relative chlorophyll content, photosynthesis rate, transpiration rate, and total chlorophyll content shifted in a variety dependent manner. However, maximum photochemical efficiency did not statistically differ between varieties impacted by saline soils. Additionally, salt exposure impacted seed yield aspects such as filled and sterile seed counts per head, total seed weight per individual flower, and 1000-seed mass, with prominent variations among the tested varieties of sunflower. Therefore, out of the six varieties of sunflower evaluated in this assessment of salt tolerance, Hysun 33 was emerged as the most resilient to adverse impacts of salinity on growth and productivity of sunflower in salinity affected regions of Bangladesh.